The Economic Role of the Family in Supporting the Recovery of People With Mental Disorders in Ringinarum Village, Kendal District - Sya Sya Nur Assa; Roofiah Adlu Khairani; Muhammad Hafizh Al Fath; Irfan Hardiansyah; Zihni Zulfahmi; Alzena Atha Rostiana; Rista Ramadina; Tazkia Zeininda Fariziany; Muhammad Faiq (Prosiding Seminar Nasional Manajemen dan Ekonomi, 2024)
Mental health is an important component of community well-being that is sometimes overlooked, especially in rural areas such as Ringinarum Sub-district, Kendal District. This report focuses on people with mental disorders (ODGJ) in the area who face various barriers, including social, economic, and access to mental health services. Based on observations and analysis, economic and social variables have a significant influence on the high frequency of mental disorders, where poverty, social stigma, and lack of support from family and community exacerbate the condition of ODGJ. This study intends to provide greater knowledge of the needs and steps that need to be taken in addressing mental health in Kecamatan Ringinarum, with data-driven suggestions to improve mental health services and de-stigmatize sufferers.